MODEL CTL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA KELAS V SDN 104/IX KEDEMANGAN - Jamalia, Jamalia (Universitas Muria Kudus, 2018)
The purpose of this research is to increase learning outcome in MTK subjects in class V. This research is a Classroom Action Research, includes: planning, implementation, and reflection, 29 study subjects consisted of 15 males and 14 females, Data collection techniques used a written assessment on the basic competence of multiplying and dividing various forms of fractions, observations in the form of indicators of teacher and student, the results showed that pre cycle of percentage of student learning outcomes that is 38%, in the first cycle increased by a percentage 72%, teacher activity by 75%, and student activity by 70% and then in the second cycle is 100% complete, with the highest 85, the lowest 75, and the average 78,97. Based on these results, it can be concluded that CTL model can improve the learning outcomes of Mtk subject of grade V students at elementary school number 104 / IX Kedemangan